THE EFFECT OF TRASH-TALKING BEHAVIOR IN DOTA 2 ONLINE GAME ON GAMERS AGGRESSIVENESS IN VERSUS CYBERSPORT PEKANBARU - Ilham Riandin; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Online games are digital games that require an internet network to access them, one of which is Defense of The Ancients 2 or commonly known as Dota 2, published by Steam Valve. Freedom in the communication facilities provided in the Dota 2 online game sometimes has a negative impact if used by irresponsible players, these communication facilities can be misused to say bad things to opponents and friends playing in online games. One example of negative actions that arise from communication facilities in online games is trash talk, namely efforts to brag, provoke, intimidate, or mentally knock opponents through verbal words or non-verbal symbols. Based on the S-R (Stimulus-Response) theory, which is a theory where communication is an action-reaction process. That is, this theory assumes that verbal words, non-verbal cues, certain symbols will stimulate others to respond in certain ways, one of which is aggressiveness, generally associated with violent or aggressive behavior (verbal and physical) such as quarrel, contention, fighting, vandalism and abuse. The purpose of this research is to see whether or not the influence of Trash-talking Behavior in Dota 2 Online Game on Gamers in Versus CyberSport Pekanbaru. The study used explanation quantitative methods. The data was collected by using questionnaires and documentation. The population of the study was gamers at Versus CyberSport Pekanbaru, amounting to 5,370 people. In determining the size of the sample, slovin formula was applied and resulted in 100 samples. The Simple Random Sampling technique was used to select the respondents. To analyze the association between the variables, the researcher applied simple linear regression analysis by using statistical software, statistic product and service solution (SPSS) Windows version 26. Based on the simple linear regression analysis, the coefficient of the regression was Y = 15.383 + 0,423X with significance level of 0,00 smaller than = 0,05. The determination test resulted in 11,9% this means that there is a very weak influence between trash-talking behavior in the online game Dota 2 on the aggressiveness of gamers in versus cybersport Pekanbaru and the remaining 88.1% is influenced by other factors outside of this study.